2010
DOI: 10.1021/ar900279d
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection of Proteins in Ancient Paint Media

Abstract: Diagnostic immunology is a powerful tool, widely used in clinical and biochemical laboratories for detecting molecules. In recent years, the technique has been adapted to materials sciences as a result of the extensive advances achieved in immunology. Today, many companies supply custom antibodies as well as new high-performance bioprobes for virtually any use. The idea of using immunodetection in the field of conservation science is not new. This analytical methodology is, in fact, particularly attractive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 40 publications
2
79
0
1
Order By: Relevance
“…21,25 In comparison with ELISA, the IFM technique can visualize the immunoreaction in situ and simplify the pretreatments of sample. 11,20,29 Similarly, to indirect ELISA, to obtain a stronger signal, an indirect method with higher sensitivity was usually applied. In this method, a non-labeled primary antibody first binds to the target protein, and then this antibody is detected by a fluorescently labeled secondary antibody, accordingly magnifying the response signals In our previous research, ELISA was firstly used to detect proteinaceous binders e.g., collagen-I and ovalbumin, in ancient silk textiles.…”
Section: Identification Of Ancient Silk Using An Enzyme-linked Immunomentioning
confidence: 99%
See 1 more Smart Citation
“…21,25 In comparison with ELISA, the IFM technique can visualize the immunoreaction in situ and simplify the pretreatments of sample. 11,20,29 Similarly, to indirect ELISA, to obtain a stronger signal, an indirect method with higher sensitivity was usually applied. In this method, a non-labeled primary antibody first binds to the target protein, and then this antibody is detected by a fluorescently labeled secondary antibody, accordingly magnifying the response signals In our previous research, ELISA was firstly used to detect proteinaceous binders e.g., collagen-I and ovalbumin, in ancient silk textiles.…”
Section: Identification Of Ancient Silk Using An Enzyme-linked Immunomentioning
confidence: 99%
“…In fact, immunological techniques are familiar to scientists due to their wide applications in biological research. [10][11][12][13][14][15][16][17] In recent years, immunological techniques have attracted increasing attention by those working in cultural heritage. For example, milk residues, 18,19 protein-bound materials and organic bones have been detected, [20][21][22][23][24][25] and all of these studies have demonstrated that immunoassays have the potential to identify and localize the proteins in archaeological materials both rapidly and effectively.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon also limits the sensitivity that can be obtained using FITC. It has also been reported that antibody conjugates prepared from FITC deteriorate over time~Vagnini et al, 2008;Cartechini et al, 2010!. The fluorophore Rhodamine B is often used in biological assays, being inexpensive and robust under a variety of reaction conditions; can be covalently linked to bioactive molecules; and has suitable spectral properties in terms of absorption and fluorescence wavelength for applications in art investigation field~Arbeloa et al, Birtalan et al, 2011!. Tetramethyl Rhodamine-Isothiocyanate~TRITC!, like LISSA, reacts with primary amines and alcohols so it can stain starches and gums as well as proteins. It is dissolved in dry acetone and gives a reddish fluorescence~Wolbers, 1990, 2000!.…”
Section: Fluorescent Staining Tests For Proteinsmentioning
confidence: 99%
“…on cross sections was reported to be successful for recognizing casein, milk, and ovalbumin in paint layers~Vag-nini et al, 2008;Pinna et al, 2009!. The immunological approach is based on the specific interaction between the antigen~protein present in the sample! and its corresponding antibody~immunoglobulin protein!~Doménech-Carbó, 2008;Vagnini et al, 2008;Sandu et al, 2009b;Cartechini et al, 2010!. Extracted antibodies can be monoclonal or polyclonal~Wild, 2005!.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Many analytical methods for the characterization of binding media (AA.VV, 2009;Mills and White, 1994;Rinuy and Gros, 1989) in polychrome works of art were developed during the past 20 years, with biochemical techniques (Cartechini et al, 2010;Dolci et al, 2008;Doménech-Carbó, 2008;Leo et al, 2009;Sandu et al, 2009) offering a useful complement to classical techniques (AA. VV, 2009;Dolci et al, 2008;Sandu et al, 2009;White, 1984) such as spectroscopy/mass spectrometry, chromatography, micro-beam, and thermoanalytical methods.…”
Section: Introductionmentioning
confidence: 99%